2005
DOI: 10.1038/sj.npp.1300825
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Dopamine Receptor Subtypes in the Medial Prefrontal Cortex of the Rat Regulate Set-Shifting

Abstract: Dopamine (DA) input to the prefrontal cortex (PFC), acting on D1 receptors, plays an essential role in mediating working memory functions. In comparison, less is known about the importance of distinct PFC DA receptor subtypes in mediating executive functions such as set-shifting. The present study assessed the effects of microinfusion of D2 and D4 receptor antagonists, and D1, D2, and D4 receptor agonists into the PFC on performance of a maze-based set-shifting task. In Experiment 1, rats were trained on a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
290
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(309 citation statements)
references
References 77 publications
17
290
2
Order By: Relevance
“…Fourth, pharmacological inactivations encompass a considerably smaller region of brain mass (B1 mm spread; see Floresco et al, 2006;Marquis et al, 2007) as compared with excitotoxic lesions (Walton et al, 2002) used in some previous studies. Such a spread would be sufficient to inactivate substantial portions of the BLA but likely only equivalent to a partial ACC lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, pharmacological inactivations encompass a considerably smaller region of brain mass (B1 mm spread; see Floresco et al, 2006;Marquis et al, 2007) as compared with excitotoxic lesions (Walton et al, 2002) used in some previous studies. Such a spread would be sufficient to inactivate substantial portions of the BLA but likely only equivalent to a partial ACC lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reconcile our results with the biochemical and the electrophysiological findings, we postulate that cooperation between the two receptor subtypes, in the same or on different neuronal population, would be required for accurate task-relevant information processing. It is worth noting that recently Floresco et al (2006) suggested that D1 and D2 dopamine receptors might cooperate within the PFC to favor setshifting. However, even if it is difficult to exclude that the effects observed in the present study could be partially due to alteration in set-shifting, if the effect observed was solely due to impairment in behavioral flexibility a reduction in the exploration of the novel object in S6 should have also been observed, in both experiments and this was not the case.…”
Section: Prefrontal Cortex Dopamine In Spatial Learningmentioning
confidence: 99%
“…The results of Ridley et al (1981) support a strong involvement of the D 2 -like receptors, as haloperidol has higher affinity for this subtype than the others. In addition, Floresco et al (2006) demonstrated that administration of the D 2 /D 3 subtype selective antagonist, eticlopride, potently impaired the ability of rats to change their behavior in response to a conditional change of rule in a set-shifting task. More direct evidence in support of these results derives from a recent study of D 2 receptor gene knockout mice.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the role of the D 1 -like receptors in behavioral flexibility is less clear. Although blockade of D 1 -like receptors in the prefrontal cortex (PFC) impaired performance of a set-shifting task, stimulation of the D 1 -like receptors in the PFC did not (Ragozzino, 2002;Floresco et al, 2006). However, it is simply unknown whether the D 1 -like receptors play a role in reversal learning, although the D 1 -like receptors are critically involved in other cognitive functions, such as working memory (Sawaguchi and Goldman-Rakic, 1991;Williams and Goldman-Rakic, 1995) and visual attention (Granon et al, 2000).…”
Section: Introductionmentioning
confidence: 99%